Virus Assembly Pathways: Straying Away but Not Too Far. Issue 51 (25th November 2020) - Bond, Kevin; Tsvetkova, Irina B.; Wang, Joseph Che‐Yen; Jarrold, Martin F.; Dragnea, Bogdan
Abstract: Non‐enveloped RNA viruses pervade all domains of life. In a cell, they co‐assemble from viral RNA and capsid proteins. Virus‐like particles can form in vitro where virtually any non‐cognate polyanionic cargo can be packaged. How only viral RNA gets selected for packaging in vivo, in presence of myriad other polyanionic species, has been a puzzle. Through a combination of charge detection mass spectrometry and cryo‐electron microscopy, it is determined that co‐assembling brome mosaic virus (BMV) coat proteins and nucleic acid oligomers results in capsid structures and stoichiometries that differ from the icosahedral virion. These previously unknown shell structures are strained and less stable than the native one. However, they contain large native structure fragments that can be recycled to form BMV virions, should a viral genome become available. The existence of such structures suggest the possibility of a previously unknown regulatory pathway for the packaging process inside cells. Abstract : When RNA viruses assemble inside a cell, they must package selectively their viral genome. How do virus capsids avoid packaging non‐cognate cargo that might out‐compete virus genomes? This work identifies differences in the structure and stoichiometry of native shells with respect to shells encapsulating nucleic acid oligomers. The differences suggest the possibility of a regulatory pathway for the packaging process.